Konflik Batin Tokoh dalam Novel Pirate Wind: Cinta, Ketamakan, dan Pengkhianatan Karya Yan Soe: Kajian Psikologi Sastra dan Implementasinya sebagai Bahan Ajar Sastra di SMA - Selawati, Dwi (2016)
The aim of the study is to describe (1) Yan Soe's social-historical background as an author, (2) the structural element of the novel, (3) the internal conflict of the main character of the novel, and (4) the result of the study will be used as a literary teaching material in High School. The type of the study is qualitative descriptive which emphasizes in the meaning of the novel. The data which are used in this study are sentences and paragraphs which show the structural element of the novel and the internal conflict of the main character of the novel. The primary data source is Yan Soe's Pirate Wind: Love, Greed, and Betrayal and the email address of the author. The technique of data collection is library research, analysis, and taking note. The technique of data analysis is heuristic and hermeneutic reading. The data validation technique in this study is the triangulation theory and triangulation data. The result of the study is: (1) the social-historical background of the author, Yan Soe as an author who likes writing about maritime history that influences his literary work. (2) Structurally the theme that is in the novel is a truly love that will destroy greed and betrayal. The characters of the novel are Lancelot, Geraldine, Richard, Rowena, Mr. Robertson, and Mrs. Robertson. The plot of the novel is progressive. The setting of place is Penang island, Fort Cornwallis, Maluku, and Malaka strain. The setting of time is 18 months or 1.5 years along 1796-1797. (3) There are three internal conflicts, Approach-Approach Conflict, Approach-Avoidance Conflict, and Avoidance- Avoidance Conflict. (4) Yan Soe's Pirate Wind: Love, Greed, and Betrayal novel can be implemented in the teaching Indonesian Language in the third grade of Senior High School.